Construction and validation of indicators and respective definitions for the nursing outcome Swallowing Status - Ana Railka de Souza Oliveira; Thelma Leite de Araujo; Emilia Campos de Carvalho; Alice Gabrielle de Sousa Costa; Tahissa Frota Cavalcante; Marcos Venícios de Oliveira Lopes (Universidade de São Paulo, 2015)
OBJECTIVE: to develop indicators for the nursing outcome Swallowing Status and the respective conceptual and operational definitions validated by experts and in a clinical setting among patients after having experienced a stroke.METHOD: methodological study with concept analysis and content and clinical validations. The Content Validation Index was verified for the scores assigned by 11 experts to indicators. Two pairs of nurses assessed 81 patients during the clinical validation: one pair used an instrument with definitions and the other used an instrument without definitions. The resulting assessments were compared using Intraclass Correlation Coefficient, Friedman's test, and Minimal Important Difference calculation.RESULTS: All the indicators, with the exception of the indicator Ability to bring food to mouth, presented Content Validation Index above 0.80. The pair using the instrument with definitions presented an Intraclass Correlation Coefficient above 0.80 for all the indicators and similarity was found in all the assessments, according to the Minimal Important Difference calculation. The pair using the instrument without definitions presented a low coefficient (ρ<0.75) for all the indicators.CONCLUSION: the results showed that greater uniformity and accuracy was achieved by the pair of nurses using the conceptual and operational definitions for the indicators of the nursing outcome Swallowing Status.